Finland finalises its largest-ever social and healthcare reform - Olli Kangas; Laura Kalliomaa-Puha (European Commission, 2022)
The Finnish government is finalising its largestever social and healthcare reform (Sote). The reform transfers responsibilities for health, social and rescue services from 309 municipalities to 22 larger organisers (21 welfare counties and the city of Helsinki). The overarching goals of this reform are to strengthen the financial basis of service delivery, to guarantee equal access to health and social services, and to reduce inequalities in health and well-being.